Laparoscopic management of benign splenic tumors in children. Issue 4 (20th July 2022) - Qingjiang, Chen; Wang, Linyan; Chen, Xiaoli; Zhang, Yuebin; Zhang, Lifeng; Zhu, Kun; Xiong, Qixing; Gao, Zhigang
Abstract : Background: The splenic tumor is relatively rare in children. However, diagnosing and managing this disease remain controversial. This study aimed to evaluate the clinical characteristics and pathological features of benign splenic tumors and to explore the feasibility and safety of laparoscopic splenectomy in children. Methods: The clinical data of all patients who were diagnosed with benign splenic tumors and admitted to our center between January 2014 and December 2020 were analyzed retrospectively. Factors that were documented included demographic criteria, clinical manifestations, preoperative examinations, surgical methods, histopathological characteristics, postoperative complications and outcomes. Results: Totally, 24 consecutive patients with a mean age of 10.21±2.59 years were operated laparoscopically. Nine patients presented with recurrent abdominal pain, vomiting or backache. The remaining 15 cases were asymptomatic and were identified incidentally. Laparoscopic total splenectomy (LTS) was performed in 12 cases, laparoscopic partial splenectomy (LPS) in 9 cases and deroofing of splenic cyst in 3 cases. No significant differences were observed in operation time, intraoperative bleeding and postoperative abdominal drainage between the LTS and LPS groups. Histopathology examination reported 12 cases of splenic epithelial cyst, 5 cases of splenic lymphangioma or lymphatic malformation, 3 cases of splenic hamartoma, 3 cases of splenic littoral cell angioma and 1 case of splenic hemangioma. No postoperative complications and tumor recurrence were observed. Conclusions: It is still difficult to precisely diagnose the splenic tumor preoperatively. Laparoscopic splenectomy is safe and feasible in treating the benign splenic tumors, and partial splenectomy is of great significance in preserving the immune function in children.